The dynamic of COVID-19 new infections under different stringent policies - Weshah A. Razzak (Economics and Econometrics Research Institute (EERI), 2020)
We estimate an unrestricted VAR to summarize the dynamics of the stringency of policy and COVID-19 infections in New Zealand, Australia, Denmark, Sweden, and the U.S. using the newly published Stringency Index by the Blavatnik School of Government at the University of Oxford, Hale et al. (2020). The stringency of the policy responds positively to the number of new infections, and new infection cases respond negatively to the increase in the stringency of the policy. New Zealand and Australia followed slightly different stringent policies, but both managed the pandemic remarkably well. Denmark, Sweden, and the U.S. adopted different policies in terms of stringency and timing. Had Denmark, Sweden, and the U.S. adopted the New Zealand's stringent policy they could have reduced the number of infection cases significantly, but not as much as in New Zealand because the stringency and timing of policy is endogenous and country-specific.
Keywords: I10; C9; C53; 330; COVID-19; Stringency Index; VAR